Design of a Flapping Aircraft with Variable Angles of Attack Based on a RC/RRU Parallel Mechanism - Wang Yujin; Hu Rui; Xia Youchang; Xu Luyou; He Miao (Jixie chuandong)
In order to simulate the flapping flight with variable angles of attack in nature, a flapping aircraft with variable angles of attack based on a RC/RRU parallel mechanism is proposed. Firstly, the model of the RC/RRU parallel mechanism is established to analyze the number of degrees of freedom and its properties, based on the screw theory. Secondly, the overall structure model of the flapping aircraft is established based on the RC/RRU parallel mechanism, and the functional relationships among the flapping angle, the angle of attack and the input angle are derived through kinematic analysis. Thus, the movement law of the flapping wing in a flapping cycle is obtained. Then, the flapping aircraft is imported into XFlow software for aerodynamic simulation for the purpose of comparing the lift and thrust performance of airfoils with different aspect ratios, so as to provide reference for airfoil design. The simulation results show that the net lift produced by the flapping aircraft is greater than the weight of the aircraft, and the lift and thrust of the airfoil with large aspect ratio are also larger. Finally, the lift and thrust test on a simple prototype is used to verify the proposed concept, and the results show that the flapping aircraft with variable angles of attack can produce effective net lift and thrust in a flapping cycle.